A Bayesian Approach to Investigating Factors Influencing Polytechnic College Students' Academic Achievement. (6th January 2022) - Getahun, Kidane A.
Abstract : TVET plays a significant role in human resource development and, as a result, in a society's progress and prosperity. The study is aiming at identifying the key factors influencing students' academic success at polytechnic colleges. The study's target population was regular Bahir Dar Polytechnic College students in the 2019/2020 academic year. Stratified random sampling was employed to conduct a cross-sectional survey of 536 participants. The author employed SPSS version 25 and WinBUGS 1.4 for quantitative data analysis. Bayesian logistic regression was used to model the factors that significantly influence TVET students' academic achievement. Gender, age, family monthly income, study hours, stimulant use during the study, English language proficiency, EGSECE score, previous perceptions of TVET, teacher satisfaction, and field of study placement satisfaction were identified as factors that significantly influenced TVET students' academic achievements. Being female, having a low family income, studying for a shorter period, using stimulants while studying, having a low English language proficiency, having a low EGSECE result, having a negative perception of TVET, and having low satisfaction with field of study were all linked to lower academic achievement in this study. According to the findings, students should spend more time in learning and consume fewer stimulants during their studies. The Ministry of Education should modify the TVET curriculum to aid students in improving their English language skills. Teachers in TVET should also receive ongoing capacity-building training. Finally, rather than imposing norms and limits (in terms of student achievement), TVET colleges should respect students' free choice of training sector (department).